1988
DOI: 10.1093/rheumatology/27.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Naproxen Dose and Concentration: Response Relationship in Rheumatoid Arthritis

Abstract: Information on the relationship between the plasma concentration of nonsteroidal anti-inflammatory drugs (NSAIDs) and clinical response in rheumatoid arthritis is sparse. As a result treatment is often relatively empirical. Standard doses are prescribed and an apparent lack of response leads either to the prescription of another drug, or an increase in the dose beyond that recommended. This study investigated 18 patients given three doses (500, 1000 and 1500 mg/day) of naproxen in a randomized double-blind des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The mean half-life was 18.5 h. Table 4 shows the pharmacokinetic parameters of naproxen after administration of a tablet of 220 mg naproxen sodium in comparison to pharmacokinetic parameters reported in previously published studies. Dose-dependent studies of naproxen in healthy volunteers after single and multiple doses observed a non- linear relationship between naproxen and plasma concentrations at higher doses [69,70]. Segre [71] reported a linear relationship between naproxen dose and plasma concentrations within 100-300 mg single dose, and a non-linear relationship at multiple doses of 375-750 mg naproxen.…”
Section: Clinical Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The mean half-life was 18.5 h. Table 4 shows the pharmacokinetic parameters of naproxen after administration of a tablet of 220 mg naproxen sodium in comparison to pharmacokinetic parameters reported in previously published studies. Dose-dependent studies of naproxen in healthy volunteers after single and multiple doses observed a non- linear relationship between naproxen and plasma concentrations at higher doses [69,70]. Segre [71] reported a linear relationship between naproxen dose and plasma concentrations within 100-300 mg single dose, and a non-linear relationship at multiple doses of 375-750 mg naproxen.…”
Section: Clinical Studymentioning
confidence: 99%
“…The plasma protein binding sites are assumed to be saturated at high naproxen doses, which results in a higher concentration of unbound naproxen and leads to a higher excretion rate and clearance [60]. This unbound naproxen concentration was shown to be proportional to naproxen concentrations at 500, 1000, and 1500 mg doses [69]. For this reason the PK parameters in Table 4 are not shown dose-corrected.…”
Section: Clinical Studymentioning
confidence: 99%
“…However, dosing regimens for NPX in treating RA have been empirical due to the lack of convincing information on the relationship between drug exposure and clinical response. The NPX concentration-response relationship in RA was explored (Dunagan et al, 1988;Day et al, 1995), but only a trend was obtained and the pharmacokinetics (PK) and pharmacodynamics (PD) of NPX were not quantitatively analyzed. Recent studies (Huntjens et al, 2006(Huntjens et al, , 2010 assessed the correlation between in vitro and in vivo exposure-effect relationships of NPX as well as the impact of chronic inflammation on the PK/PD of NPX.…”
Section: Introductionmentioning
confidence: 99%
“…However, such a relationship exists in adult rheumatoid arthritis (Day et al 1982): 75% of 22 patients with serum naproxen concentrations of 55 to 92 mg/L responded to the therapy. Interestingly, clinical effects appear to parallel total concentration more closely than unbound concentration (Dunagan et al 1988), which may be attributable to the observed nonlinearity in the protein binding of naproxen (Runkel et al 1974).…”
Section: 2 Propionic Acid Derivativesmentioning
confidence: 97%